Health and Counseling Service of Reproductive Health “I am Empowered Over my Body” - Suhaid, Dewi Novitasari; Aningsih, Baharika Suci Dwi; Dini, Kusuma; Kadarsih, Mitra; Purbo, Yoshepine Beni (Universitas Ibn Khaldun, 2024)
Reproductive health is a crucial aspect of improving the quality of life, especially for women of reproductive age. However, knowledge about reproductive health, including early detection of breast and cervical cancer, remains low in many communities. Limited access to reproductive health services, particularly in remote and economically disadvantaged areas, exacerbates this issue. This community service program aimed to enhance public awareness and provide direct health services through the Reproductive Health Service and Counseling under the theme